A case-control study of cataract in Oxfordshire: some risk factors. Issue 11 (November 1988) - van Heyningen, R; Harding, J J
Abstract : Three hundred patients with cataract and 609 control subjects with the same age-sex distribution were interviewed in a study of cataract in Oxfordshire, England. The risks associated with severe diarrhoea, glaucoma, and work on a military base have been demonstrated. Population attributable risks were calculated for those and other risk factors.